HPA-1 and HPA-3 Polymorphisms of the Platelet Fibrinogen Receptor and Coronary Artery Disease and Myocardial Infarction - Böttiger, Corinna; Kastrati, Adnan; Koch, Werner; Mehilli, Julinda; Seidl, Holger; Schömig, Kathrin; von Beckerath, Nicolas; Schömig, Albert (Thrombosis and Haemostasis, 2000)
Platelet fibrinogen receptor (glycoprotein [GP] IIb/IIIa) plays a fundamental role in atherothrombosis. The human platelet antigen (HPA) -1 and the HPA-3 are the most extensively studied polymorphisms of GPIIIa and GPIIb, respectively. This study was designed to test, in a large population, the hypothesis that these polymorphisms represent a risk factor for the occurrence of coronary artery disease (CAD) and myocardial infarction (MI).Consecutive, angiographically examined patients with significant coronary stenoses but without symptoms or signs of old or acute MI constituted the group with CAD (CAD, n = 998) and those with old or acute MI constituted the group with MI (MI, n = 793). As controls served subjects, matched with patients for age and sex, with neither angiographic CAD nor symptoms or signs of MI (matched controls [MC], n = 340) as well as a group of blood donors without cardiac symptoms or signs of CAD (BD, n = 104). Genotype distribution was similar across the groups; HPA-1a/a: HPA-1a/b: HPA-1b/b was 75.0%: 22.1%: 2.9% in BD, 72.6%: 24.7%: 2.6% in MC, 70.5%: 26.8%: 2.7% in CAD, and 70.7%: 26.4%: 2.9% in MI; HPA-3a/a: HPA-3a/b: HPA-3b/b was 39.4%: 40.4%: 20.2% in BD, 33.5%: 50.0%: 16.5% in MC, 35.0%: 46.4%: 17.0% in CAD, and 37.1%: 48.0%: 16.5% in MI. There was no interaction between these polymorphisms, nor between each of these polymorphisms and other risk factors.Thus, the HPA-1 and HPA-3 polymorphisms are neither separately nor in concert associated with any measurable increase of the risk for CAD or MI in angiographically evaluated subjects.
Keywords: Coronary artery disease; myocardial infarction; platelets; fibrinogen receptor; genetics